Digital connectivity & e-commerce: Overview of financing flows and examples of aid for trade support - Theo Mbise; Sainabou Taal; Michael Roberts; Frans Lammersen (World Trade Organization (WTO), 2018)
Digital networks are an increasingly critical component of global trade. In 2017, the Global Review of Aid for Trade highlighted the importance of accessible and affordable connections for trade connectivity. Drawing extensively on information harvested in the Monitoring and Evaluation exercise in preparation for the Review, this paper analyses aid for trade for digital connectivity and e-commerce. Also presented in this paper are the types of issues and challenges faced in cross-border electronic transactions - an area in which demand for support is set to grow. The paper also surveys flows reported to the Organisation for Economic Cooperation and Development Creditor Reporting System. Funds disbursed to digital connectivity amounted to US6.6 billion in concessional financing and US8.3 billion in non-concessional financing in the period 2006-2016. The top providers of financing were the European Union, Japan, Korea, the United Kingdom and the World Bank Group. The paper also highlights the various methodological difficulties encountered, and explains the need to further refine reporting definitions so as to better capture financing flows to digital connectivity and to understand how aid for trade is being used to leverage private sector financing for ICT. The analysis concludes by reviewing the catalytic role that aid for trade is playing in mobilizing private sector financing. Research for the 2017 Global Review suggests that both developing countries and donors view ICT connectivity as an area where demand for financing will grow in future.
Keywords: F35; P33; P45; L81; O33; 330; aid for trade; digital connectivity; ICT connectivity; e-commerce